El futuro y la lectura del pasado. Historias dignas de naciones dignas. - Alvarenga Venutolo, Patricia (2012)
This article is based on the discourse of Guatemalan and Salvadoran thinkers of the first decades of the XX Century. It explores, in past indigenous narrations, the axis that give sense to an identitary construction of a hybrid self. The concept of race is a fundamental key in the identity construction. Therefore, this article analyzes how the intellectuals shape a history that let them to rescue the indigenous world from the ominous inferiority attributed to colonial nations. Within the context of the closely related concepts of race and civility, it is intended to apprehend the choice of common narrative patterns used to put to together the history of the ancestral natives, a history that also records the becoming of the Central American nations.